Examination of Perceived Health and Healthy Lifestyle Behaviors by Pharmacists in Elazig - Kurt, Osman; Özdemir, Betül Yiğit; Açıkkapu, Mehmet Akif; Deveci, Süleyman Erhan (My University, 2022)
Objective: The study aimed to investigate the Healthy Lifestyle Behavior (HLSB) and perceived health levels in pharmacists, who are important healthcare professionals, and the factors that affected these parameters.\rMaterials and Methods: A two-part questionnaire was applied to 132 pharmacists included in this cross-sectional study. In the first part, a questionnaire consisting of sociodemographic characteristics, factors thought to affect healthy lifestyle behaviors and perceived health-related questions was applied, and in the second part, a questionnaire consisting of the HLPS Scale was applied.\rResults: Based on the perceived health scale, 73.5% rated their health as good (excellent/very good/good) and 26.5% as bad (moderate/bad). It was determined that HLSB scale score of those who were satisfied with their profession was higher than those who were not, of those who did not smoke was higher than those who did, of those who exercised regularly was higher than those who did not, of those who did not have sleep problems was higher than those who did, and of those who consider themselves healthy was higher than those who did not (p<0.05). \rConclusion: It was determined that the mean HLSB of the participating pharmacists was moderate and one fourth of the pharmacists considered themselves as unhealthy based on the perceived health scale.
Keywords: Perceived health; Healthy lifestyle behavior; pharmacist